Assessment of left ventricular function in patients with type 2 diabetes mellitus by non-invasive myocardial work - Cao, Wenjia; Deng, Yan; Lv, Linyi; Liu, Xuebing; Luo, Anguo; Yin, Lixue; Li, Zhaohuan (Frontiers in Endocrinology, 2023)
Background: Diabetes mellitus (DM) is a chronic disease that poses a serious risk of cardiovascular diseases. Therefore, early detection of impaired cardiac function with non-invasive myocardial imaging is critical for improving prognosis of DM patients. Purpose: This study aimed to assess the left ventricular (LV) function in patients with type 2 diabetes mellitus (T2DM) by noninvasive myocardial work technique. Materials and Methods: Sixty-seven patients with T2DM and twenty-eight healthy controls were included and divided into DM group and control group. Two-dimensional dynamic images of apical three chamber view, apical two chamber view, and apical four chamber view were collected from all subjects, consisting of at least three cardiac cycles. LV myocardial strain parameters, including global longitudinal strain (GLS) and peak strain dispersion (PSD), as well as myocardial work parameters, including global constructive work (GCW), global wasted work (GWW), global work index (GWI), and global work efficiency (GWE) were obtained and analyzed.Results: Fifteen subjects were randomly selected to assess intra-observer and inter-observer consistency of myocardial work parameters and strain parameters, which showed excellent (intra-class correlation coefficients: 0.856 -0.983, P<0.001).Compared with the control group, the DM group showed significantly higher PSD (37.59±17.18 ms vs. 27.72±13.52 ms, P<0.05) and GWW (63.98±43.63 mmHg% vs. 39.28±25.67 mmHg%, P<0.05), and lower GWE (96.38±2.02% vs. 97.72±0.98%, P<0.001). Furthermore, the PSD was positively correlated with GWW (r = 0.565, P<0.001) and negatively correlated with GWE (r = -0.569, P<0.001). Conclusion: Uncoordinated LV myocardial strain, higher GWW, and lower GWE in patients with T2DM may serve as indictors for the early assessment of cardiac impairment in T2DM.